(The Effect of Extraction Methode to the Yield and Curcumin Content from Curcuma (Curcuma Xanthoriza Roxb) - Eko Susanto (Warta Industri Hasil Pertanian, 2001)
A study to find out the best condition in extraction of curcumin from curcuma xanthoriza has been conducted the variable the used are the solvent concentration methode of extraction ,and material and solvent proportion .the result showed that semi continues process by using alcohol 95% and proportion between material with solvent 1:8 produced the highest curcumin content .the yield has total dissolved solid 11,48% with 1.502% curcumin.